ATTITUDE OF THE YUGOSLAV STATE LEADERSHIP TO THE MACEDONIAN-SERBIAN CHURCH DISPUTE IMMEDIATELY AFTER PROCLAMATION OF THE AUTOCEPHALITY OF THE MACEDONIAN ORTHODOX CHURCH (Annual of the Faculty of Philosophy in Skopje, 2010)
The proclamation of the autocephality of the Macedonian Orthodox Church on the Third ecclesiastical-national assembly in June 1967 caused strong reactions of the bishop of the Serbian Orthodox Church, which were transferred in the Decisions on the extraordinary meeting of the assembly in September 1967. The deteriorated relations between the Serbian and Macedonian Orthodox Church were very often on the agenda of the Federal Commission for Religious Affairs before the proclamation of the autocephality of the Macedonian Orthodox Church and even more afterwards. In the discussions with the Serbian Patriarch German the representatives of the Federal Executive Council pointed out that the matter of the proclamation of the autocephality of the Macedonian Orthodox Church is not only an ecclesiastical-canonical bat primarily a national and political problem. Just one year after the proclamation of the autocephality of the Macedonian Orthodox Church the members of the Federal Commission for Religious Affairs realized that the patriarch and the Synod explicitly refused any attempt to normalize relations between the two churches, consistently maintaining the position that the Macedonian Orthodox Church can only be part of the Serbian Orthodox Church. This matter also was often discussed on the sessions of the Republican Committees on Religious Affairs in Macedonia and Serbia.
Keywords: FEDERAL EXECUTIVE COUNCIL; MACEDONIAN ORTHODOX CHURCH; FEDERAL COMMISSION FOR RELIGIOUS AFFAIRS; SERBIAN ORTHODOX CHURCH; AUTOCEPHALITY; REPUBLICAN COMMITTEE ON RELIGIOUS AFFAIRS